The Effect of Heating Irrigation Water on the Growth and Development of Cucumber Plants Grown in the Winter Season - Aml Adrees Abdulsalam (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
This study looks into what happens to cucumber plants when they are watered with warm water in the winter. For the study, cucumber plants were split into two groups: one got water that was warm, and the other didn't. The plants in the hot watering group grew faster than the plants in the control group. They were taller, had bigger leaves, flowers earlier, and had more fruits per plant. The group that used hot water also had a higher total yield weight per plant. The findings show that heating irrigation water makes it just right for the roots. This facilitates nutrient absorption in plants, alleviates stress, and accelerates development, particularly under cold conditions. This information is beneficial for cultivators in temperate regions; nevertheless, more research is required to ascertain its impact on soil health, energy use, and potential integration with other crops in the future.